2012
DOI: 10.3136/fstr.18.543
|View full text |Cite
|
Sign up to set email alerts
|

Development of Gluten-Free Bread baked with Yam Flour

Abstract: Gluten-free bread baked with yam flour (Jinennjyo; Dioscorea japonica), wheat starch, sugar (sucrose), compressed yeast, and water showed similar bread making properties, such as bread height (mm) and specific volume (cm 3 /g), to that of wheat bread. Yam flour was dialyzed against water and separated into nondialyzable (high-molecular-weight (HMW)) fraction and dialyzable (low-molecular-weight (LMW)) fractions. The fractions were dried and used separately in bread making in the same manner. The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Small deformation rheology was measured in nine out of 22 references (Aguilar et al, 2015;Juszczak et al, 2012;Korus et al, 2012;Minarro et al, 2012;van Riemsdijk et al, 2011a;Witczak et al, 2010;Ziobro et al, 2013b). Large deformation was used four times (Korus et al, 2012;Seguchi et al, 2012;van Riemsdijk et al, 2011a;. The pasting properties in batter/dough during heating as measured by RVA or Mixolab were determined by Witczak et al (2010;, Juszczak et al (2012) and Krupa-Kozak et al (2012;.…”
Section: Analyses Of Batter/dough and Breadmentioning
confidence: 99%
“…Small deformation rheology was measured in nine out of 22 references (Aguilar et al, 2015;Juszczak et al, 2012;Korus et al, 2012;Minarro et al, 2012;van Riemsdijk et al, 2011a;Witczak et al, 2010;Ziobro et al, 2013b). Large deformation was used four times (Korus et al, 2012;Seguchi et al, 2012;van Riemsdijk et al, 2011a;. The pasting properties in batter/dough during heating as measured by RVA or Mixolab were determined by Witczak et al (2010;, Juszczak et al (2012) and Krupa-Kozak et al (2012;.…”
Section: Analyses Of Batter/dough and Breadmentioning
confidence: 99%
“…A very common use of purple yam is the substitution of wheat flour for bakery products and food products in general without affecting the sensorial acceptance of the products by consumers [225][226][227], while yam flour can be used for gluten-free bakery products [228].…”
Section: Yammentioning
confidence: 99%
“…This was a similar formula to wheat sweet dough for coffee sweet bread. Seguchi et al [11] reported that they could obtain a nice bread making properties such as bread height and specific volume (68.4 mm and 3.95 cm 3 /g) using yam flour (10 g). Seguchi et al [12] also obtained same nice bread height and specific volume, 69.4 mm and 3.45 cm 3 /g, respectively in banana flour (30 g).…”
Section: Optimal Amounts Of Ingredients For Bread Making With Gagome mentioning
confidence: 99%